2014
DOI: 10.1002/jcb.24748
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 Activation Ameliorates Renal Fibrosis by Inhibiting the TGF‐β/Smad3 Pathway

Abstract: TGF-β signaling plays an important role in the pathogenesis and progression of chronic kidney disease (CKD). Smad3, a transcription factor, is a critical fibrogenic mediator of TGF-β. Sirt1 is a NAD(+) -dependent deacetylase that has been reported to modify a number of transcription factors to exert certain beneficial health effects. This study examined the effect of Sirt1 on Smad3 and its role in CKD. Resveratrol attenuated the expression of extracelluar matrix proteins in both the remnant kidney of 5/6th nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 50 publications
(73 reference statements)
9
175
0
1
Order By: Relevance
“…Furthermore, the results of an in vivo study indicated that RSV increases SIRT1 expression and stimulates PGC-1a activity in skeletal muscle (24). The results of the present study demonstrate that RSV is able to mitigate the STZ-induced inhibition of SIRT1, PGC-1α and FOXO3a, which is in accordance with previous results (25)(26)(27). A number of previous studies have reported that INS resistance is associated with mitochondrial dysfunction (22) and these results may be caused by oxidative stress (28).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of an in vivo study indicated that RSV increases SIRT1 expression and stimulates PGC-1a activity in skeletal muscle (24). The results of the present study demonstrate that RSV is able to mitigate the STZ-induced inhibition of SIRT1, PGC-1α and FOXO3a, which is in accordance with previous results (25)(26)(27). A number of previous studies have reported that INS resistance is associated with mitochondrial dysfunction (22) and these results may be caused by oxidative stress (28).…”
Section: Discussionsupporting
confidence: 92%
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014). In this study, we found that aging suppressed SIRT1 activity, increased TGFβ and MMP expressions, and induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has been shown to exert tissue-specific effects with regard to its ability to regulate tissue fibrosis. SIRT1 inhibits TGF-␤-mediated renal fibrosis and blocks the epithelial-to-mesenchymal transition that leads to organ fibrosis (61,62). In contrast to this, other studies report that SIRT1-deficient hearts develop reduced fibrosis following stress, while SIRT1-overexpressing hearts develop massive fibrosis with age (19,63).…”
Section: Sirt3 Activates Gsk3␤mentioning
confidence: 94%